2021
DOI: 10.1007/s00265-021-02966-w
|View full text |Cite
|
Sign up to set email alerts
|

Food level and light conditions affect the antipredator behavior in larvae of a stream-breeding amphibian

Abstract: Understanding how long-term changes in environmental conditions influence the way that individuals cope with threats is essential in the context of behavioral adaptation to a rapidly changing world. However, little is known about the behavioral responses to predation risk for individuals that experienced different environmental conditions for extended periods of time, such as food levels and light conditions. In this experimental study, we tested whether previous long-term exposure to different food levels (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Likewise, in our experiment, N. thuringius individuals were more active during night, when all microcosms were completely dark. Differences in diel activity are expected to occur in organisms with activity patterns regulated by the photoperiod (Bancila et al 2021;Falcón et al 2020) and it is worth noting that in our experiment responses to day period and light were detected in the stygobiont amphipod, but not in the epigean one. Furthermore, the interaction between day period and predation risk highlighted that during night-time, stygobionts were more active in tanks without predation risk than in those with predators.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Likewise, in our experiment, N. thuringius individuals were more active during night, when all microcosms were completely dark. Differences in diel activity are expected to occur in organisms with activity patterns regulated by the photoperiod (Bancila et al 2021;Falcón et al 2020) and it is worth noting that in our experiment responses to day period and light were detected in the stygobiont amphipod, but not in the epigean one. Furthermore, the interaction between day period and predation risk highlighted that during night-time, stygobionts were more active in tanks without predation risk than in those with predators.…”
Section: Discussionmentioning
confidence: 47%
“…Furthermore, the interaction between day period and predation risk highlighted that during night-time, stygobionts were more active in tanks without predation risk than in those with predators. Similarly, Bancila et al (2021) detected a complex interplay between light conditions and environmental features, including not only predation risk, but also food availability, in shaping activity of salamander larvae. Interactive effects of night/light conditions with environmental features suggest that the differences observed between field and laboratory conditions could be linked to the complex and difficult to be controlled interplay of multiple factors acting on spring ecotones in the wild.…”
Section: Discussionmentioning
confidence: 95%
“…Our results did not support this assumption, as the traits we investigated were responsive to food availability and light condition, but no interaction between these two factors was detected. However, a previous study ( Băncilă et al, 2021 ) showed that these two factors have an interactive effect on the behavioural responses of fire salamander larvae; more specifically, larvae exposed to low food availability take more risks in exploring the environment, especially in the absence of light, when predator pressure would be lower. Manenti, Denoël & Ficetola (2013) found that behavioural plasticity is higher in larvae from subterranean environments.…”
Section: Discussionmentioning
confidence: 96%
“…We exposed larvae from different altitudes to either rich or poor food availability levels and observed the effects on both larval and juvenile growth, and on juvenile behaviour (food stimulus response). Previous studies showed that nutritional conditions experienced at the larval stage may have complex behavioural and morphological consequences (Bancila et al, 2021; Krause & Caspers, 2016) that can last and impact for years after metamorphosis (Krause et al, 2021). Here, we investigated if responses to food treatments at different life stages reflected adaptation to the different conditions along the altitudinal gradient.…”
Section: Introductionmentioning
confidence: 99%